Effect of the Law Enforcement Duty Belt on Muscle Activation during Hip Hinging Movements in Young, Healthy Adults - James W. Kearney; Megan N. Sax van der Weyden; Nelson Cortes; Orlando Fernandes; Joel R. Martin (Journal of Functional Morphology and Kinesiology, 2023)
Sixty percent of all law enforcement officers (LEOs) experience low back pain (LBP), with the LEO duty belt (LEODB) commonly reported to be a contributing factor. The primary purpose of the study was to investigate the LEODB’s effect on muscular activity and compare it to a tactical vest, which is a commonly used alternative to an LEODB. In total, 24 participants (13 male, 11 female; mass, 73.0 ± 11.1 kg; height, 169.0 ± 10.0 cm; age, 24.0 ± 5.8 years) completed a progressive series of hip hinge tasks in a single testing session. All participants completed four conditions (no belt, leather belt, nylon belt, and weight VEST) in a randomized order. Surface electromyography (sEMG) sensors were placed bilaterally on the rectus abdominus, multifidus, biceps femoris, and rectus femoris. Across all tasks, no significant effects of load on muscle activity were found for any of the muscles. Participants rated the VEST condition as more comfortable (p < 0.05) and less restrictive (p < 0.05) than either LEODB. The findings suggest an LEODB does not alter muscle activity during bodyweight hip hinging or lifting objects from the ground. Future research should examine whether changes in muscle activity occur with durations of LEODB wear more similar to an actual work shift duration for LEOs (≥8 h).